Method for supermolecule-assisted synthesis of ferrous sulfide / nitrogen-sulfur co-doped carbon composite material and application

The preparation of ferrous sulfide/nitrogen-sulfur co-doped carbon composite materials through supramolecular assisted synthesis method has solved the problems of complex preparation processes and poor lithium storage performance in the prior art, and achieved simple controllable preparation and efficient storage of composite materials Lithium performance.

CN119481044APending Publication Date: 2025-02-18HUNAN INSTITUTE OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411754021.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the application of lithium-ion battery negative electrodes, there are complex preparation processes, low raw material utilization rate, difficulty in mass production, large size of ferrous sulfide particles, limited conductive contact and poor lithium storage performance. question.

Method used

Using supramolecular assisted synthesis method, the supramolecular is formed through the interaction between melamine and cyanuric acid, and then reacts with iron and sulfur sources. After calcination and ultrasonic dispersion, ferrous sulfide/nitrogen sulfur co-doping is prepared. Heterocarbon composite material.

Benefits of technology

The preparation process of composite materials is simple, controllable, and can be mass-produced on a large scale. Ferrous sulfide is uniformly dispersed in the carbon substrate, effectively inhibiting agglomeration. The carbon substrate has rich porous structure and co-doping of nitrogen and sulfur. , significantly improves lithium storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481044A_ABST
    Figure CN119481044A_ABST
Patent Text Reader

Abstract

The invention relates to a method for supermolecule-assisted synthesis of a ferrous sulfide / nitrogen-sulfur co-doped carbon composite material and application, and the specific steps are as follows: firstly, melamine and cyanuric acid construct a supermolecule precursor through molecular self-assembly, and after an iron source is added, the supermolecule precursor is calcined in an inert atmosphere; the calcined product is coated with nitrogen-containing macromolecules, then a sulfur source is added for annealing treatment, and finally the ferrous sulfide / nitrogen-sulfur co-doped carbon composite material is prepared. Compared with the prior art, the preparation method has the following benefits: the composite material is simple in preparation process, high in controllability and easy for large-scale production; the prepared ferrous sulfide / nitrogen-sulfur co-doped carbon composite material has a relatively large specific surface area, a rich porous structure and active sites; when the material is used as a lithium ion battery negative electrode material, relatively high lithium storage capacity and excellent cycling stability can be shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ferrous sulfide composite materials, and in particular to a method and application of supramolecular assisted synthesis of ferrous sulfide / nitrogen-sulfur co-doped carbon composite materials. Background Art

[0002] With the rapid development of electronic products and energy storage devices, people have a growing demand for rechargeable and dischargeable lithium-ion batteries with no memory effect, small size, light weight and high safety. However, the limited theoretical specific capacity of commercial graphite anodes restricts their application in large-scale energy storage devices. Compared with embedded graphite anodes, conversion transition metal sulfide anodes have attracted widespread attention from researchers due to their higher theoretical specific capacity.

[0003] As a typical representative of metal sulfides, ferrous sulfide has a high theoretical specific capacity and has the advantages of being environmentally friendly, low-priced, and having abundant raw materials. However, when it is used as the negative electrode of lithium-ion batteries, it faces a series of problems such as low conductivity, obvious volume effect, and serious agglomeration. The composite of ferrous sulfide and carbon materials is regarded as an effective strategy to improve its lithium storage performance. Through the modification of carbon materials, not only the conductivity of the material can be improved, but also ferrous sulfide can be loaded, dispersed or coated, thereby alleviating the volume effect and agglomeration phenomenon to a certain extent. It can be seen that ferrous sulfide / carbon composite materials show potential application prospects in the field of lithium-ion battery negative electrodes.

[0004] Patent CN 112310379A discloses a preparation method and application of a carbon nanotube-loaded ferrous sulfide micron electrode material. The preparation method comprises the following steps: (1) adding iron salt and deionized water to a reaction bottle to prepare a salt solution, placing the solution in an ice water bath under nitrogen protection, and stirring to obtain solution A; (2) adding sodium borohydride and sodium hydroxide to deionized water, mixing, slowly adding the solution to solution A, stirring, aging and standing to obtain a standing solution B; (3) adding sublimated sulfur, urea and multi-walled carbon nanotube slurry to the standing solution B, stirring to obtain solution C, and keeping warm at 140-180°C; (4) centrifuging the product, washing with distilled water and anhydrous ethanol, and vacuum drying to obtain a carbon nanotube-loaded ferrous sulfide micron electrode material.

[0005] However, it has the following disadvantages: the preparation process is complicated (for example, carbon nanotubes need to undergo purification, acidification, grinding and other processes), the raw material utilization rate is low, it is difficult to mass produce, and explosive tube products such as sodium borohydride are used; the ferrous sulfide particles in the composite material are large in size (up to the micron level), and the volume effect is significant during the charging and discharging process; the conductive contact between carbon nanotubes and ferrous sulfide is limited, making it difficult to achieve effective coating, and the carbon nanotubes are not doped with non-metals, so the improvement in the lithium storage performance of the composite material is limited.

[0006] Patent CN 113517486 A discloses a porous carbon / ferrous sulfide composite material and its preparation method and application, which specifically includes the following steps: (1) dismantling waste lithium iron phosphate batteries, taking out the positive electrode sheets, separating the aluminum foil and the positive electrode materials in the positive electrode sheets, and leaching the collected positive electrode materials with a hydrochloric acid solution to obtain a hydrochloric acid leaching solution containing lithium and iron; (2) pretreating the cation exchange resin with a hydrochloric acid solution, and pretreating the anion exchange resin with a sodium chloride solution or a hydrochloric acid solution; (3) using cation and anion exchange resins to separate the iron and lithium in the acid leaching solution of the waste lithium iron phosphate positive electrode material, wherein the lithium remains in the effluent and the iron is enriched in the resin; (4) activating the cation exchange resin waste material that has adsorbed iron to saturation with an alkali solution, and then placing the cation exchange resin waste material that has adsorbed iron to saturation in different calcined boats, and the two calcined boats are simultaneously placed in a high-temperature tubular furnace for calcination to prepare a porous carbon / ferrous sulfide composite material.

[0007] However, it has the following disadvantages: the preparation process is complicated (including discharge, disassembly, acid leaching of waste lithium iron phosphate batteries and ion exchange resin pretreatment, adsorption, crushing, screening and other processes), the cost of ion exchange resin is high, the adsorption capacity is limited, and it is difficult to achieve large-scale mass production; the coating effect between ferrous sulfide and carbon material in the prepared composite material is not good, the carbon material is not doped with non-metals, the lithium storage performance is poor, and the material specific capacity after 150 cycles is only 258.6 mAh / g. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method and application of a supramolecular assisted synthesis of ferrous sulfide / nitrogen-sulfur co-doped carbon composite material for lithium ion battery negative electrode field. The present invention has the advantages of simple preparation process, strong controllability, and large-scale preparation.

[0009] In order to achieve the purpose of the present invention, the following technical solutions are provided: A method for supramolecular assisted synthesis of ferrous sulfide / nitrogen-sulfur co-doped carbon composite material, characterized in that it comprises the following steps: Step (1) weighing 1.0-2.0 g of melamine and dissolving it in 40-60 mL of dimethyl sulfoxide, heating it to 50-70°C, stirring and dissolving it to obtain a melamine solution; weighing 1.0-2.0 g of cyanuric acid and dissolving it in 20-40 mL of dimethyl sulfoxide, heating it to 50-70°C, stirring and dissolving it to obtain a cyanuric acid solution; Step (2) dropping the melamine solution obtained in step (1) into the cyanuric acid solution, stirring for 20 to 30 minutes, centrifuging and washing with deionized water for 3 to 5 times, and drying the solid obtained by centrifugation at 60° C. in vacuum to obtain melamine-cyanuric acid supramolecular MCA; Step (3) mixing the melamine-cyanuric acid supramolecular MCA obtained in step (2) with an iron source in a mass ratio of (5-20):1, and then calcining in nitrogen at 400-600°C for 2-3 h to obtain a calcined product; Step (4) ultrasonically dispersing the calcined product obtained in step (3) in 100 mL of deionized water, then sequentially adding 0.1-1.0 mL of a nitrogen-containing small molecule monomer, 5-10 mL of a 12 M HCl solution, and 1.0-2.0 g of an initiator, and stirring the mixture under ice bath conditions for 10-24 h; after the reaction is completed, centrifuging the mixture, washing it with deionized water for 3-5 times, and vacuum drying it to obtain a black powder; Step (5) The black powder obtained in step (4) is mixed with a sulfur source in a mass ratio of 1:(15-20), and the temperature is raised to 700-900°C at a rate of 5-15°C / min in nitrogen, and calcined at a constant temperature for 1-3 h to finally obtain a ferrous sulfide / nitrogen-sulfur co-doped carbon FeS@NSC composite material.

[0010] Preferably, the iron source is one or more of ferric chloride, ferric nitrate, ferric acetate, and ferric sulfate; Preferably, the nitrogen-containing small molecule monomer is one or more of pyrrole, aniline, indole and dopamine.

[0011] Preferably, the initiator is one or more of ferric chloride, ammonium persulfate, hydrogen peroxide, and potassium dichromate.

[0012] Preferably, the sulfur source is one or more of sulfur powder, thiourea, thioacetamide, and hydrogen sulfide.

[0013] The present invention has the following beneficial effects: (1) The preparation process of the composite material of the present invention is simple, highly controllable, and can be prepared in large quantities on a large scale; (2) In the composite material prepared by the present invention, ferrous sulfide is uniformly dispersed and anchored in the carbon substrate, which effectively suppresses its agglomeration problem; the carbon substrate has a rich porous structure and successfully achieves nitrogen-sulfur co-doping; the composite material has broad application prospects in the field of lithium-ion battery negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The scanning electron microscope image (a), transmission electron microscope image (b), high-resolution transmission electron microscope image (c), scanning transmission electron microscope image (d) and corresponding element distribution diagrams (e–i) of the FeS@NSC (1:0.1) composite material prepared in Example 1 of the present invention; Figure 2The X-ray diffraction pattern (a) and Raman spectrum (b) of the FeS@NSC (1:0.1) composite material prepared in Example 1 of the present invention; Figure 3 is a general X-ray photoelectron spectrum of the FeS@NSC (1:0.1) composite material prepared in Example 1 of the present invention; Figure 4 is a cycle performance diagram of the FeS@NSC (1:0.1) composite negative electrode prepared in Example 1 of the present invention; Figure 5 is a rate performance diagram of the FeS@NSC (1:0.1) composite negative electrode prepared in Example 1 of the present invention; Figure 6 is a scanning electron microscope image of the FeS@NSC (1:0.05) composite material prepared in Example 2 of the present invention; Figure 7 The X-ray diffraction pattern (a) and Raman spectrum (b) of the FeS@NSC (1:0.05) composite material prepared in Example 2 of the present invention; Figure 8 is a general X-ray photoelectron spectrum of the FeS@NSC (1:0.05) composite material prepared in Example 2 of the present invention; Fig. 9 is a cycle performance diagram of the FeS@NSC (1:0.05) composite negative electrode prepared in Example 2 of the present invention; Fig.10 This is a rate performance diagram of the FeS@NSC (1:0.05) composite negative electrode prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0015] In the description of the present invention, the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or the positions or positional relationships in which the inventive product is usually placed when in use. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0016] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "link" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0017] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be noted that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of application of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid confusion of the concept of the present invention. Example 1

[0018] Weigh 1.0 g of melamine and dissolve it in 40 mL of dimethyl sulfoxide, heat it to 60 °C, stir and dissolve it to obtain a melamine solution; weigh 1.0 g of cyanuric acid and dissolve it in 20 mL of dimethyl sulfoxide, heat it to 60 °C, stir and dissolve it to obtain a cyanuric acid solution. Drop the melamine solution into the cyanuric acid solution, stir it for 20 min, centrifuge it, wash it with deionized water 3 times, and dry it at 60 °C in a vacuum to obtain a white powder. Take 1 g of the above white powder, add 0.1 g of Fe(NO3)3·9H2O, grind it thoroughly, transfer it to a tube furnace, and anneal it at 550 °C for 3 h under a nitrogen atmosphere. Weigh 200 mg of the above calcined product, and ultrasonically disperse it with 150 μL of pyrrole in 100 mL of deionized water, then add 5 mL of 12 M HCl solution and 1.5 g of ammonium persulfate in sequence, react it under ice bath conditions for 12 h, centrifuge it, and wash it with deionized water 3 times. The separated product was vacuum dried, mixed with sulfur powder in a mass ratio of 1:16, and calcined at 750 °C for 2 h in a nitrogen atmosphere to finally obtain the FeS@NSC (1:0.1; this value represents the mass ratio of MCA and Fe source) composite material.

[0019] See also Figure 1 ,like Figure 1The following are the scanning electron microscope images (a), transmission electron microscope images (b–c), scanning transmission electron microscope images (d) and corresponding element distribution images (e–i) of the prepared FeS@NSC (1:0.1) composite material. As shown in Figure (a), the FeS nanosheets are uniformly embedded or dispersed in the carbon substrate; Figure (b) further confirms its existence; Figure (c) shows the obvious lattice fringes of FeS; Figures (e–i) show the existence of C, N, O, Fe and S elements, and the N and S elements are uniformly distributed on the carbon substrate, proving the successful doping of the two elements.

[0020] See also Figure 2 ,like Figure 2 The X-ray diffraction pattern (a) and Raman spectrum (b) of the prepared FeS@NSC (1:0.1) composite material are shown. As shown in Figure (a), the composite material exhibits typical FeS characteristic diffraction peaks, proving the successful synthesis of FeS; as shown in Figure (b), the Raman spectrum of the composite material has two characteristic peaks, D band and G band, and their intensity ratio is as high as 1.00, indicating that the carbon matrix in the composite material has a high degree of structural defects.

[0021] See also Figure 3 ,like Figure 3 The figure shows the X-ray photoelectron spectrum of the prepared FeS@NSC (1:0.1) composite material. Figure 3 It can be seen that the composite material contains C, N, O, Fe and S elements at the same time, among which the contents of N and S elements are 10.92% and 9.98%, respectively, which further indicates that the carbon matrix has successfully achieved nitrogen and sulfur co-doping.

[0022] See also Figure 4 ,like Figure 4 The figure shows the cycle performance of the prepared FeS@NSC (1:0.1) composite negative electrode. Figure 4 It can be seen that at 0.1 A g –1 At the current density of 955.2 mAh g, the composite anode still exhibited a capacity of 955.2 mAh g after 200 cycles. –1 reversible specific capacity.

[0023] See also Figure 5 As shown in the figure, the rate performance diagram of the prepared FeS@NSC (1:0.1) composite negative electrode. Figure 4 It can be seen that the composite negative electrode has good conductivity at current densities of 0.1, 0.2, 0.4, 0.5 and 1.0 A g –1 When the capacities were 1232.5, 1053.4, 930.1, 863.1 and 793.1 mAh g –1 The discharge capacity is 0.1 A g –1 When the specific capacity is restored to 1245.5 mAh g–1 , indicating its excellent rate performance. Example 2

[0024] Weigh 1.0 g of melamine and dissolve it in 50 mL of dimethyl sulfoxide, heat it to 60 °C, stir and dissolve it to obtain a melamine solution; weigh 1.0 g of cyanuric acid and dissolve it in 30 mL of dimethyl sulfoxide, heat it to 60 °C, stir and dissolve it to obtain a cyanuric acid solution. Drop the melamine solution into the cyanuric acid solution, stir it for 30 min, centrifuge it, wash it with deionized water 3 times, and dry it at 60 °C in a vacuum to obtain a white powder. Take 1 g of the above white powder, add 0.05 g of Fe(NO3)3·9H2O, grind it thoroughly, transfer it to a tube furnace, and anneal it at 550 °C for 3 h under a nitrogen atmosphere. Weigh 200 mg of the above calcined product, and ultrasonically disperse it with 150 μL of pyrrole in 100 mL of deionized water, then add 5 mL of 12 M HCl solution and 1.5 g of ammonium persulfate in sequence, react it under ice bath conditions for 24 h, centrifuge it, and wash it with deionized water 3 times. The separated product was vacuum dried, mixed with sulfur powder in a mass ratio of 1:16, and calcined at 750 °C for 2 h in a nitrogen atmosphere to finally obtain the FeS@NSC (1:0.05; this value represents the mass ratio of MCA and Fe source) composite material.

[0025] See also Figure 6 ,like Figure 6 The following is a scanning electron microscope image of the prepared FeS@NSC (1:0.05) composite material. Figure 6 It can be seen that there is almost no obvious FeS phase, indicating that most of the FeS is embedded in the carbon matrix.

[0026] See also Figure 7 ,like Figure 7 The X-ray diffraction pattern (a) and Raman spectrum (b) of the prepared FeS@NSC (1:0.05) composite material are shown. As shown in Figure (a), almost no obvious FeS characteristic diffraction peaks can be detected. This result may be due to the complete coverage of the FeS phase by the carbon matrix. As shown in Figure (b), the ratio of the D band and G band intensity of the composite material is 0.99, indicating that the carbon matrix in the composite material has a high degree of structural defects.

[0027] See also Figure 8 , as shown in the figure is the X-ray photoelectron spectrum of the prepared FeS@NSC (1:0.05) composite material. Figure 8 It can be seen that the composite material contains five elements, namely C, N, O, Fe and S, at the same time, indicating that FeS and NSC phases may have been successfully synthesized.

[0028] See also Fig. 9 ,like Fig. 9 The figure shows the cycle performance of the prepared FeS@NSC (1:0.05) composite negative electrode. Fig. 9 It can be seen that at 0.1 A g –1 At the current density of 1:0.05, the FeS@NSC composite anode exhibited a capacity of 600.1 mAh g after 190 cycles. –1 reversible specific capacity.

[0029] See also Fig.10 ,like Fig.10 The figure shows the rate performance of the prepared FeS@NSC (1:0.05) composite anode. Fig.10 It can be seen that the composite negative electrode has good conductivity at current densities of 0.1, 0.2, 0.4, 0.5 and 1.0 A g –1 When the –1 The discharge capacity is 0.1 A g –1 When the specific capacity is restored to 888.0 mAh g –1 , indicating its good rate performance.

Claims

1. A method for supramolecularly assisted synthesis of ferrous sulfide / nitrogen-sulfur co-doped carbon composite materials, characterized in that: The steps include: Step (1) weighing 1.0-2.0 g of melamine and dissolving it in 40-60 mL of dimethyl sulfoxide, heating it to 50-70°C, stirring and dissolving it to obtain a melamine solution; weighing 1.0-2.0 g of cyanuric acid and dissolving it in 20-40 mL of dimethyl sulfoxide, heating it to 50-70°C, stirring and dissolving it to obtain a cyanuric acid solution; Step (2) dropping the melamine solution obtained in step (1) into the cyanuric acid solution, stirring for 20 to 30 minutes, centrifuging and washing with deionized water for 3 to 5 times, and drying the solid obtained by centrifugation at 60° C. in vacuum to obtain melamine-cyanuric acid supramolecular MCA; Step (3) mixing the melamine-cyanuric acid supramolecular MCA obtained in step (2) with an iron source in a mass ratio of (5-20):1, and then calcining in nitrogen at 400-600°C for 2-3 h to obtain a calcined product; Step (4) ultrasonically dispersing the calcined product obtained in step (3) in 100 mL of deionized water, then sequentially adding 0.1-1.0 mL of a nitrogen-containing small molecule monomer, 5-10 mL of a 12 M HCl solution, and 1.0-2.0 g of an initiator, and stirring the mixture under ice bath conditions for 10-24 h; after the reaction is completed, centrifuging the mixture, washing it with deionized water for 3-5 times, and vacuum drying it to obtain a black powder; Step (5) The black powder obtained in step (4) is mixed with a sulfur source in a mass ratio of 1:(15-20), and the temperature is raised to 700-900°C at a rate of 5-15°C / min in nitrogen, and calcined at a constant temperature for 1-3 h to finally obtain a ferrous sulfide / nitrogen-sulfur co-doped carbon FeS@NSC composite material.

2. The method for supramolecular-assisted synthesis of ferrous sulfide / nitrogen-sulfur co-doped carbon composite materials according to claim 1, characterized in that: The iron source is one or more of ferric chloride, ferric nitrate, ferric acetate and ferric sulfate.

3. The method for supramolecular-assisted synthesis of ferrous sulfide / nitrogen-sulfur co-doped carbon composite materials according to claim 1, characterized in that: The nitrogen-containing small molecule monomer is one or more of pyrrole, aniline, indole and dopamine.

4. The method for supramolecular-assisted synthesis of ferrous sulfide / nitrogen-sulfur co-doped carbon composite materials according to claim 1, characterized in that: The initiator is one or more of ferric chloride, ammonium persulfate, hydrogen peroxide and potassium dichromate.

5. The method for supramolecular-assisted synthesis of ferrous sulfide / nitrogen-sulfur co-doped carbon composite materials according to claim 1, characterized in that: The sulfur source is one or more of sulfur powder, thiourea, thioacetamide and hydrogen sulfide.

6. Use of the ferrous sulfide / nitrogen-sulfur co-doped carbon composite material prepared by the method according to any one of claims 1 to 5, characterized in that: Used in negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method and application of carbon nanotube loaded ferrous sulfide micron electrode material

    CN112310379A

  • Porous carbon / ferrous sulfide composite material as well as preparation method and application thereof

    CN113517486A